Figure 7 in New species and global revision of Hippasteria (Hippasterinae: Goniasteridae; Asteroidea; Echinodermata) - Mah, Christopher; Neill, Kate; Eléaume, Marc; Foltz, David (Zenodo, 2014)
Figure 7. Hippasteria phrygiana (North Atlantic, South Pacific). USNM 14361 North Atlantic. Scale bar = 1.0 cm. A, abactinal surface. B, actinal surface. C, marginal plate series. USNM E13768 New Zealand. D, abactinal surface. E, marginal plate series. F, actinal surface showing furrow and mouth spines. G and H show USNM E46619 and MNHN (Paris) EcAs 10683, respectively, at R = ∼4.5–5.0. I, CASIZ 113374 British Columbia. J, CASIZ 173038 Aleutians. Lateral view showing abactinal spines, pedicellariae, and marginal plates. : Published as part of Mah, Christopher, Neill, Kate, Eléaume, Marc & Foltz, David, 2014, New species and global revision of Hippasteria (Hippasterinae: Goniasteridae; Asteroidea; Echinodermata), pp. 422-456 in Zoological Journal of the Linnean Society 171 (2) on page 442, DOI: 10.1111/zoj.12131, http://zenodo.org/record/4890583